Problem based learning with geogebra: Impact on mathematical communication skills and mathematical problem solving - Amallya, Eva; Anggoro, Bambang Sri; Fadila, Abi (Fakultas Tarbiyah dan Ilmu Keguran IAIN Metro, 2025)
Students' mathematical communication and mathematical problem solving are still weak because the average test results are still below the KKM. Seeing this, the author conducted a study using the Problem Based Learning learning model. The goal is for students to be able to solve a mathematical problem properly and correctly. This study uses a quantitative approach with a quasi-experimental research type with a post-test only control group research design. The sample in this study were students in grades XI IPA I and XI IPA 2 with a simple random sampling technique. The data collection technique in this study was a test. The prerequisite techniques used were multivariate normality and homogeneity tests and hypothesis testing in this study used the Multivariate Analysis Of Variance (Manova) test. The results of the study showed that there was an influence of the GeoGebra-assisted Problem Based Learning approach on the mathematical communication and mathematical problem solving abilities of high school students and on the mathematical communication and mathematical problem solving abilities of students, there was a better influence of the GeoGebra-assisted Problem Based Learning learning model compared to conventional learning models.